AN ANALYSIS OF DISSOCIATIVE IDENTITY DISODER (DID) EXPERIENCED BY KEVIN IN THE MOVIE “SPLIT” - Bejo Sutrisno; meilina Meilina (Journal of English Language and Literature (JELL), 2020)
This study is under psychology umbrella. The aim of this study is to analyze Dissociative Identity Disorder experience by Kevin, the main character in the movie Split. This study has two objectives: (1) to find out what are the symptoms or signs of DID on Kevin in the movie Split; (2)to find out how does Dissociative Identity Disorder effect the main character’s life. This study employed a qualitative method since it describing the phenomena of DID. Moreover, the findings were presented in narrative or textual description. Some steps in analyzing the data were : watch the movie, taking notes, sorting the data, classifying the data, coding the data, interpretation, and the last drawing conclusion. This study reveals two findings, first, all of four classification symptoms in Kevin. Second, three effects of this disorder has coming up to main charcater live (Kevin) were : depersonalization or derealization, amnesia, identity confusion or identity alteration.